Rapamycin Improved Retinal Function and Morphology in a Mouse Model of Retinal Degeneration - Zhao, Meng; Lv, Houting; Yang, Na; Peng, Guang-Hua (Frontiers in Neuroscience, 2022)
The retina is an important visual organ, which is responsible for receiving light signals and transmitting them to the optic nerve center step by step. The retina contains a variety of cells, among which photoreceptor cells receive light signals and convert them into nerve signals, and are mainly responsible for light and dark vision. Retinal degeneration is mainly the degeneration of photoreceptor cells, and retinitis pigmentosa (RP) is characterized by rod degeneration followed by cone degeneration. So far, there is still a lack of effective drugs to treat RP. Here, we established a stable RP model by tail vein injection of methyl methanesulfonate (MMS) to study the mechanism of retinal photoreceptor degeneration. Mechanistic target of rapamycin (mTOR) is located in the central pathway of growth and energy metabolism and changes in a variety of diseases in response to pathological changes. We found that the mTOR was activated in this model. Therefore, the inhibitor of mTOR, rapamycin was used to suppress the expression of mTOR and interfere with photoreceptor degeneration. Electroretinogram (ERG) assay showed that the function of mice retina was improved. Hematoxylin and eosin (HE) staining results displayed that retinal photoreceptor thickness and morphology were improved. Also, the autophagy in rapamycin group was activated, which revealed that rapamycin may protect the retinal photoreceptor by inhibiting mTOR and then activating autophagy.